2018
DOI: 10.1007/s00421-018-4027-4
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation does not influence the neural adjustments associated with fatiguing contractions in a hand muscle

Abstract: Purpose The objective of the current study was to investigate the mechanisms responsible for the briefer time to failure of a submaximal contraction (C2) when performed 60 min after a similar contraction (C1), and the influence of anodal transcranial direct current stimulation (a-tDCS) applied over the motor cortex on these mechanisms. Methods In two sessions, ten adults sustained two isometric contractions (35% of maximum) to failure with the abductor pollicis brevis (APB). Before C2, either a-tDCS or sham st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
0
18
1
Order By: Relevance
“…Furthermore, no significant change was noted in the activation level of the dominant flexor and extensor muscles after tDCS treatment, which was consistent with the results of muscle strength in this study. Some studies have determined that tDCS will not further heighten muscle function after it has reached a maximum level ( Lattari et al, 2016 ; Abdelmoula et al, 2019 ). Considering that the subjects selected in this study were all right leg dominant, the muscle activation level has reached the best state in high-intensity exercise, and in this state, the ability of tDCS to increase the number of motor unit recruitment to improve the muscle activation degree might be limited, resulting in no significant improvement in muscle strength performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no significant change was noted in the activation level of the dominant flexor and extensor muscles after tDCS treatment, which was consistent with the results of muscle strength in this study. Some studies have determined that tDCS will not further heighten muscle function after it has reached a maximum level ( Lattari et al, 2016 ; Abdelmoula et al, 2019 ). Considering that the subjects selected in this study were all right leg dominant, the muscle activation level has reached the best state in high-intensity exercise, and in this state, the ability of tDCS to increase the number of motor unit recruitment to improve the muscle activation degree might be limited, resulting in no significant improvement in muscle strength performance.…”
Section: Discussionmentioning
confidence: 99%
“…(2) There is no consensus on the effects of tDCS on upper limb motor performance, and the quantitative analysis samples included in this meta-analysis were too few, which would lead to the possibility of false negative or false-positive results in our synthesis. (3) In the study of upper limb endurance, only two articles (Abdelmoula et al, 2016(Abdelmoula et al, , 2018 focused on the dominant side. Although the results showed that tDCS had no significant effect on improving the muscle endurance of the dominant side of the upper limb, we were cautious about this result due to the lack of samples.…”
Section: Limitationmentioning
confidence: 99%
“…Similarly, in terms of muscle endurance, some studies found that tDCS had no effect on upper limb muscle endurance (Kan et al, 2013;Muthalib et al, 2013;Radel et al, 2017;Abdelmoula et al, 2018). For example, Abdelmoula et al (2018) found no significant change in time to exhaustion (TTE) after a-tDCS stimulation during thumb abduction at 35% MIVC by applying a 1.5 mA, 10 min tDCS stimulation to the left M1. In contrast, another study found that tDCS could increase the TTE (Cogiamanian et al, 2007;Williams et al, 2013;Abdelmoula et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of papers have drawn attention to the large variability in response to tDCS both between and within individuals, with several studies failing to observe any net effects ( Abdelmoula et al, 2019 ; Lopez-Alonso et al, 2014 ; Lopez-Alonso et al, 2015 ; Vannorsdall et al, 2016; Wiethoff et al, 2014 ; Wiltshire and Watkins, 2020 ; Wrightson et al, 2020 ). The discrepancies probably arise because, as noted above, the results of tDCS depend on so many factors, including the precise orientation neuronal/synaptic populations and current flow, the intensity of current in each individual, and the effects of ongoing (or past) brain states, or individual genetic susceptibility.…”
Section: Modulating Brain Activity (Tdcs and Tacs)mentioning
confidence: 99%